Ca2+-Clock-Dependent Pacemaking in the Sinus Node Is Impaired in Mice with a Cardiac Specific Reduction in SERCA2 Abundance - Logantha, Sunil Jit R. J.; Stokke, Mathis K.; Atkinson, Andrew J.; Kharche, Sanjay R.; Parveen, Sajida; Saeed, Yawer; Sjaastad, Ivar; Sejersted, Ole M.; Dobrzynski, Halina (Frontiers in Physiology, 2016)
Background: The sarcoplasmic reticulum Ca2+-ATPase (SERCA2) pump is an important component of the Ca2+-clock pacemaker mechanism that provides robustness and flexibility to sinus node pacemaking. We have developed transgenic mice with reduced cardiac SERCA2 abundance (Serca2 KO) as a model for investigating SERCA2’s role in sinus node pacemaking. Methods and Results: In Serca2 KO mice, ventricular SERCA2a protein content measured by Western blotting was 75% (P<0.05) lower than that in control mice (Serca2 FF) tissue. Immunofluorescent labelling of SERCA2a in ventricular, atrial, sinus node periphery and centre tissue sections revealed 46%, 45%, 55% and 34% (all P<0.05 vs. Serca2 FF) lower labelling, respectively and a mosaic pattern of expression. With telemetric ECG surveillance, we observed no difference in basal heart rate, but the PR-interval was prolonged in Serca2 KO mice: 49±1 vs. 40±1 ms (P<0.001) in Serca2 FF. During exercise, heart rate in Serca2 KO mice was elevated to 667±22 bpm, considerably less than 780±17 bpm (P<0.01) in Serca2 FF. In isolated sinus node preparations, 2 mM Cs+ caused bradycardia that was equally pronounced in Serca2 KO and Serca2 FF (32±4% vs. 29±5%), indicating no change in If. Disabling the Ca2+-clock with 2 μM ryanodine induced bradycardia that was less pronounced in Serca2 KO preparations (9±1% vs. 20±3% in Serca2 FF; P<0.05), suggesting a disrupted Ca2+-clock. Mathematical modelling was used to dissect the effects of membrane and Ca2+-clock components on Serca2 KO mouse heart rate and sinus node action potential. Computer modelling predicted a slowing of heart rate with Serca2 downregulation and the heart rate slowing was pronounced at >70% Serca2 downregulation. Conclusions: Serca2 KO mice show a disrupted Ca2+-clock-dependent pacemaker mechanism contributing to impaired sinus node and atrioventricular node function.